If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + -1)(x) = 3(x)(x) + x(x + -1) Reorder the terms: 2(-1 + 2x)(x) = 3(x)(x) + x(x + -1) Reorder the terms for easier multiplication: 2x(-1 + 2x) = 3(x)(x) + x(x + -1) (-1 * 2x + 2x * 2x) = 3(x)(x) + x(x + -1) (-2x + 4x2) = 3(x)(x) + x(x + -1) Multiply x * x -2x + 4x2 = 3x2 + x(x + -1) Reorder the terms: -2x + 4x2 = 3x2 + x(-1 + x) -2x + 4x2 = 3x2 + (-1 * x + x * x) -2x + 4x2 = 3x2 + (-1x + x2) Reorder the terms: -2x + 4x2 = -1x + 3x2 + x2 Combine like terms: 3x2 + x2 = 4x2 -2x + 4x2 = -1x + 4x2 Add '-4x2' to each side of the equation. -2x + 4x2 + -4x2 = -1x + 4x2 + -4x2 Combine like terms: 4x2 + -4x2 = 0 -2x + 0 = -1x + 4x2 + -4x2 -2x = -1x + 4x2 + -4x2 Combine like terms: 4x2 + -4x2 = 0 -2x = -1x + 0 -2x = -1x Solving -2x = -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -2x + x = -1x + x Combine like terms: -2x + x = -1x -1x = -1x + x Combine like terms: -1x + x = 0 -1x = 0 Divide each side by '-1'. x = 0 Simplifying x = 0
| 36-4x-3x=22 | | m-7=-13 | | 8-(3+6)=b-9 | | x-14=-8 | | 5n+4=-36 | | 10z-3-7z=9 | | 2(2x+1)(x)=3(x)(x)+x(x-1) | | 4h-10=-2 | | 2c+30=10-2 | | 0.4x-2.3=1.3 | | 9u-3=-3 | | 8x+6x^2=0 | | (x-4)(x)+(2x+1)=(x)(x)-(4-x) | | 2m^2-7m-23=0 | | (x-14)(x)+(2x+1)=(x)(x)-(4-x) | | 2m^2-7m-23=10 | | 2b+4=-18 | | 0.45x+.05(10-x)=.10(45) | | 5x^2-30=95 | | -x-3-2x=9 | | (21x+3)=(14x+2) | | 5x-4x=12 | | x+x+24+2x-35=713 | | 2=11-3n | | 3x=-1.2x+8.4 | | (4x^3)-(9x^2)=0 | | x+1100=y | | 7x+13y-23=0 | | 2x+520=y | | (x-4)(x)+(2x-1)=x^2-(4-x) | | x-1/6=-5/3 | | -x+8+9x+6=-18 |